Understanding Public Participation in Thailand’s Khon Kaen Light Rail Transit Project through the COM–B Framework: A Behavioral Science Perspective - Panyavaranant, Peeranun; Jotaworn, Surasak (Social Science Innovation and Applied Management (SIAM), 2025)
For transportation planning to be truly inclusive and effective, public participation plays a significant role. However, various structural and behavioral barriers often cause engagement levels to fluctuate. This study explored the influencing factors on public involvement in urban infrastructure projects, using Thailand’s Khon Kaen Light Rail Transit (LRT) project as a case study. This study applies the COM–B framework as the conceptual lens to identify key behavioral factors influencing citizen participation. A quantitative survey of 505 residents who living along the LRT route was conducted. The questionnaire used in the survey was developed based on the COM–B model to assess respondents’ knowledge, motivation, and access to participation channels. To study the relationship between behavioral factors and the level of participation, data were analyzed statistically using regression analysis, Spearman correlation, and descriptive statistics. The findings reveal that capability (ρ = 0.632) and opportunity (ρ = 0.524) were significantly statistical associated with participation levels, while motivation shows a weaker correlation (ρ = 0.124). To improve participatory, the study highlighted the importance on educational initiatives which enhanced by digital participation platforms and strategies to build the public trust. Thus, integrating scientific and behavioral perspectives into transportation planning can provide valuable insights for policymakers. The public awareness can improve accessibility, trust building, and leading to more equitable and successful transportation projects. The study also contributed empirical evidence for designing more inclusive and participatory urban development policies in Thailand and comparable contexts